Natural Bioactive Compounds in the Management of Type 2 Diabetes and Metabolic (Dysfunction)-Associated Steatotic Liver Disease - Daniela Ciobârcă; Adriana Florinela Cătoi; Laura Gavrilaș; Roxana Banc; Doina Miere; Lorena Filip (Pharmaceuticals)
Type 2 diabetes (T2D) and metabolic (dysfunction)-associated steatotic liver disease (MASLD) affect a growing number of individuals worldwide. T2D and MASLD often coexist and substantially elevate the risk of adverse hepatic and cardiovascular clinical outcomes. Several common pathogenetic mechanisms are responsible for T2D and MASLD onset and progression, including insulin resistance, oxidative stress, and low-grade inflammation, among others. The latter can also be induced by gut microbiota and its derived metabolites. Natural bioactive compounds (NBCs) have been reported for their therapeutic potential in both T2D and MASLD. A large amount of evidence obtained from clinical trials suggests that compounds like berberine, curcumin, soluble fibers, and omega-3 fatty acids exhibit significant hypoglycemic, hypolipidemic, and hepatoprotective activity in humans and may be employed as adjunct therapy in T2D and MASLD management. In this review, the role of the most studied NBCs in the management of T2D and MASLD is discussed, emphasizing recent clinical evidence supporting these compounds’ efficacy and safety. Also, prebiotics that act against metabolic dysfunction by modulating gut microbiota are evaluated.